2011
DOI: 10.1371/journal.ppat.1002176
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection Induces Expression of Novel Phased MicroRNAs from Conserved Cellular MicroRNA Precursors

Abstract: RNA silencing, mediated by small RNAs including microRNAs (miRNAs) and small interfering RNAs (siRNAs), is a potent antiviral or antibacterial mechanism, besides regulating normal cellular gene expression critical for development and physiology. To gain insights into host small RNA metabolism under infections by different viruses, we used Solexa/Illumina deep sequencing to characterize the small RNA profiles of rice plants infected by two distinct viruses, Rice dwarf virus (RDV, dsRNA virus) and Rice stripe vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(166 citation statements)
references
References 81 publications
8
150
1
4
Order By: Relevance
“…3A). It has been reported that RSV infection induced the expression of OsRDR1 in rice (Satoh et al, 2010;Du et al, 2011). As we have shown that RSV infection induced the accumulation of miR444 (Fig.…”
Section: Overexpression Of Mir444 Increases Rice Resistance Against Vsupporting
confidence: 72%
See 1 more Smart Citation
“…3A). It has been reported that RSV infection induced the expression of OsRDR1 in rice (Satoh et al, 2010;Du et al, 2011). As we have shown that RSV infection induced the accumulation of miR444 (Fig.…”
Section: Overexpression Of Mir444 Increases Rice Resistance Against Vsupporting
confidence: 72%
“…RDR1 orthologs have been reported to be virus or salicylic acid inducible in different plants, including Arabidopsis, Nicotiana spp., Medicago truncatula, maize (Zea mays), and rice (Oryza sativa; Yang et al, 2004;Alamillo et al, 2006;He et al, 2010;Satoh et al, 2010;Du et al, 2011), and to provide basal resistance to several viruses by participating in the biogenesis of virusderived secondary siRNAs (Diaz-Pendon et al, 2007;Qi et al, 2009;Garcia-Ruiz et al, 2010;Wang et al, 2010). Recently, it was reported that RDR1 also is responsible for the production of a distinct class of virus-activated siRNAs, which direct widespread silencing of host genes to confer broad-spectrum antiviral activity in Arabidopsis (Cao et al, 2014), indicating that RDR1 plays a key role in antiviral resistance by silencing both the viral RNAs and the host immunity-related genes.…”
mentioning
confidence: 99%
“…] differentially induced by pathogen infection is the first step to investigate their functions in host immunity against the pathogen. Previously, a set of miRNAs were identified to be involved in plant immunity against bacterial and viral pathogens (Navarro et al, 2006;Du et al, 2011;Radwan et al, 2011;Seo et al, 2013). Recently, host miRNAs were also found to be responsive to the infection of an increasing list of filamentous pathogens, such as Cronartium quercuum (Lu et al, 2007), Erysiphe graminis (Xin et al, 2010), Fusarium virguliforme (Radwan et al, 2011), Phytophthora sojae (Guo et al, 2011), and Verticillium dahliae (Yin et al, 2012;Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Coimmunoprecipitation with FLAG-and HA-specific antibodies was used to obtain (ix) AGO1 and (x) AGO2 complexes, respectively, from the FLAG-AGO1/ago1-36 and HA-AGO2 plants 14 d after infection with Fny CMV-Δ2b for extracting total loaded small RNAs for the construction and sequencing of small RNA libraries as described (52). Bioinformatic analysis was carried out as described previously (13,15,53). Briefly, small RNAs in the size range of 18-26 nt were used for further analysis after removing the adaptor sequences.…”
Section: Methodsmentioning
confidence: 99%